Evaluation of wound healing process based on texture analysis - Kasparis, Takis; Mitsi, Orthodoxia; Loizou, Christos P. (My University, 2012)
Wound healing rate, remains an interesting and important issue, in which modern imaging techniques have not yet given a definitive answer. In order to guide better therapeutic interventions, a better understanding of the fundamental mechanisms driving tissue repair are required. The wound healing rate is primarily quantified by the rate of change of the wound's surface area. The objective of this study was to establish a standardised and objective technique to asses the progress of wound healing in foot by means of texture analysis. The methods of image pre-processing, segmentation and texture analysis together with visual expert's evaluation were used to assess the wound healing process. A total of 40 digital images from ten different subjects with food wounds were taken every third day, for 12 days, by an inexpensive digital camera under variable lighting conditions. The images were intensity normalized, and wounds were automatic segmented using a snake's segmentation system. From the segmented wounds 15 different texture characteristics and 4 different geometrical features were extracted in order to identify features that quantify the rate of wound healing. We found texture characteristics that may indicate the progression of wound healing process. More specifically, some texture features increase (mean, contrast), while some other texture features decrease (entropy, sum of squares variance, sum average, sum variance) with the progression of the wound healing process. Some of these features were found to be significantly different in a specific time point and this could be used to indicate the rate of wound healing. No significant differences were found for all geometrical measures. The results of this study suggest that some texture features might be used to monitor the wound healing process, thus reducing the workload of experts, provide standardization, reduce costs, and improve the quality for patients. The simplicity of the method also suggests that it may be a valuable tool in clinical wound evaluation. Future work will incorporate additional texture and geometrical features for assessing the wound healing process in order to be used in the real clinical praxis.
Keywords: Entropy; Wounds and injuries; Digital cameras; Texture (Art)